Viewpoint by Guest Writers : Halal issues in processed food: Misuse of the Halal logo / Faridah Hj. Hassan and Azlina Hanif. - Hassan (Haji), Faridah; Hanif, Azlina (Universiti Teknologi MARA Selangor, 2017)
Professor Dr Faridah Hj Hassan is a professor of Marketing and Strategic Management from Arshad Ayub Graduate Business School, Universiti Teknologi MARA, Shah Alam. She is a prolific writer and researcher in the areas of Halal food marketing and branding, Islamic tourism and strategic management. Her passion in Halal branding lends her an important role as the Director of iHalal Management and Science, FBM, UiTM. Dr Azlina Hanif is a senior lecturer of Economics from Arshad Ayub Graduate Business School, Universiti Teknologi MARA. Her research interest is in the areas of International Trade and Islamic Economics. She is currently doing research on the research performance of universities in South East Asia under the ERASMUS+ program.